Microscope-aided endodontic treatment of maxillary first premolars with three roots: A case series - C S Karumaran (Indian Journal of Dental Research, 2011)
Maxillary premolars have a highly variable root canal morphology. However, the presence of three roots is a rare occurrence. This clinical article describes the unusual anatomy detected in maxillary premolars during routine endodontic treatment using microscope. The diagnosis and clinical management of maxillary first premolars with three roots and canals using radiographic interpretation, access cavity modification and visual enhancement with operative microscopes is discussed in the article.